Natural Gas, Public Investment and Debt Sustainability in Mozambique - Melina, Giovanni; Xiong, Yi. (Washington, D.C. : International Monetary Fund, 2013)
Mozambique has great potential in natural gas reserves and if liquefied/commercialized the sum of taxes and other fiscal revenue from natural gas will, at its peak, reach roughly one third of total fiscal revenue. Recent developments in the natural resource sector have triggered a fresh round of much needed infrastructure investment. This paper uses the DIGNAR model to simulate alternative public investment scaling-up plans in alternative LNG market scenarios. Results show that while a conservative approach, which simply awaits LNG revenues, would miss significant current growth opportunities, an aggressive approach would likely meet absorptive capacity constraints and imply a much bigger (and, in an adverse scenario, unsustainable) build-up of public debt. A gradual scaling up approach represents indeed a desirable path, as it allows anticipating some, though not all, of the LNG revenue and, even in an adverse scenario, keeping public debt at sustainable levels. Structural reforms affecting selection, governance and execution of public investment projects would significantly enhance the extent to which public capital is accumulated and impact non-resource growth and, ultimately, debt sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet